Effect of revegetation and of fertilization of degraded area on prodution of dry matter and on nutrient uptake - Favaretto, Nerilde; Moraes, Aníbal de; Motta, Antônio Carlos Varga; Prevedello, Beatriz Monte Serrat (Pesquisa Agropecuaria Brasileira, 2000)
This work was carried out on degraded area by oil shale mining, to evaluate the effect of different fertilizations and revegetations with forage species on the total dry production and the macronutrients concentration and extraction by plants. The experiment was conducted for 12 months at São Mateus do Sul, Paraná State, Brazil, in a randomized block with split plots design, being three plots related to fertilization and three subplots related to forage species. The fertilizations used were: I - mineral fertilizer with aerial part left over; II - mineral and organic fertilizer with aerial part removed; III - mineral fertilizer with aerial part removed. Forage composed the following systems: Systems I and II - perennial grasses and legumes species of summer and winter; System III - annual grasses and legumes species of summer and winter. The evaluations were related to dry matter and concentration and extraction by plant of P, K, Ca, Mg, C and N. It was observed greatest dry matter production in the treatment with organic fertilization and with annual forages, and that the extraction of nutrients by plants was, in general, superior in treatments with high dry matter production.